Ischnura elegans malikovae subspecies nova (Odonata, Coenagrionidae) from the Far East of Eurasia, with discussion of other possible subspecies - Onishko, Vladimir V.; Kosterin, Oleg E. (Zootaxa, 2022)
Ischnura elegans malikovae ssp. n. is described from the southern Far East of Russia (type locality: Russia, Primorskiy Kray, Pozharskiy District, Luchegorsk Town, the Luchegorsk Reservoir). Reconsideration of literature suggested it to broadly range in East Asia including Korea, Japan (Hokkaido and northernmost Honshu), north and north-east China and to be hitherto mistaken for Ischnura elegans elegans (Vander Linden, 1820) in Japan. The main difference of the new subspecies from I. e. elegans is the male paraprocts that are about 1.5 times shorter and scarcely divaricating in dorsal view and directed obliquely upward in lateral view. Ischnura elegans ebneri Schmidt, 1938 is reconsidered as the presumably Anterior Asian subspecies characterised by scarcely or not diverging male paraprocts in dorsal view, versus strongly diverging in I. e. elegans. Based on scarce information in the literature, I. elegans marquardti Schmidt, 1938 is supposed to be a junior synonym of I. elegans ordosi Bartenev, 1912 stat. rev., which is suggested to be an eastern Central Asian subspecies characterised by an incised prothoracic process in males.